2021
DOI: 10.1016/j.jhep.2021.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge and management of portal vein thrombosis in cirrhosis

Abstract: Portal vein thrombosis (PVT) is an increasingly recognised complication of cirrhosis whose incidence increases in parallel with the severity of cirrhosis. Several risk factors have been associated with the occurrence and progression of PVT. Although the negative effect of complete PVT on the surgical outcome of liver transplant recipients is clear, its impact on cirrhosis progression remains uncertain. Treatment options include anticoagulants and interventional thrombolytic therapies, which are chosen almost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
150
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(179 citation statements)
references
References 132 publications
(181 reference statements)
3
150
1
3
Order By: Relevance
“…( 21 ) In patients without liver disease, increased activation of coagulation is one of the main factors responsible for the increased thrombotic tendency in patients with cancers. ( 20 , 36 ) While awaiting large prospective trials to establish whether alterations of hemostasis are truly implicated in the pathogenesis of PVT in patients with cirrhosis, ( 5 , 6 ) and to further confirm the association between HCC and increased thrombotic tendency in these patients, we performed a case‐control study to investigate alterations of coagulation in this patient population. Because hemostasis in cirrhosis is complex, ( 1 , 3 ) and altered fibrinolysis may also be responsible for the thrombotic tendency in digestive cancers, ( 19 , 37 ) we included determination not only of coagulation but also of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…( 21 ) In patients without liver disease, increased activation of coagulation is one of the main factors responsible for the increased thrombotic tendency in patients with cancers. ( 20 , 36 ) While awaiting large prospective trials to establish whether alterations of hemostasis are truly implicated in the pathogenesis of PVT in patients with cirrhosis, ( 5 , 6 ) and to further confirm the association between HCC and increased thrombotic tendency in these patients, we performed a case‐control study to investigate alterations of coagulation in this patient population. Because hemostasis in cirrhosis is complex, ( 1 , 3 ) and altered fibrinolysis may also be responsible for the thrombotic tendency in digestive cancers, ( 19 , 37 ) we included determination not only of coagulation but also of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…(6) On the other hand, the pathogenesis of PVT in cirrhosis is multifactorial and likely results from alterations in one or more components of the Virchow's triad (i.e., decreased portal vein inflow, hypercoagulability, and local damage of the portal vein wall). (5) Therefore, it is plausible that a more profound hypercoagulable state, at least in some patients, could contribute to the development of this thrombotic complication. (5) Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer occurring in patients with cirrhosis, (7) and is associated with a purported increased risk of thrombosis, particularly PVT.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of PVT in cirrhosis is multifactorial and results mainly from alterations in the different components of Virchow's triad: reduced portal blood flow, a hypercoagulable state, or vascular endothelial injury (Figure 2). 22 Recent studies have reported that cirrhosis patients with portal blood flow less than 15 cm/s were at increased risk of developing PVT. 23,24 In addition, an increase in portal blood inflow through portosystemic collaterals also seems to influence PVT development.…”
Section: Pathophysiology Of Portal Vein Thrombosismentioning
confidence: 99%